A study of linguistic politeness strategies in expressing love in english versus vietnamese - Đỗ Thị Thùy Loan (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Cross-gender communication has attracted increasing attention from scholars in different fields. In this paper, linguistic politeness strategies used in expressing love by different genders in English and Vietnamese is studied thoroughly with valuable contributions from sociolinguistics, pragmatics, semantics, syntax and cultural studies. This study is on the basis of Face Study of Brown and Levinson, Politeness Principles of Leech in association with Social-Norm on Politeness. The basic view of this paper is that there are differences between men’s and women’s verbal politeness strategies in expressing love and that these differences originate from different gender cultures. Using the contrastive analysis of 200 samples from English and Vietnamese films, we could find that women tend to use Direct Strategies at higher frequency than men and Conventionally Indirect Strategies tend to be preferred by native English speakers than by native Vietnamese speakers. These differences can cause many difficulties in communication for English learners of Vietnamese and Vietnamese learners of English as a foreign language. We hope that the findings of this study could provide a deeper insight into the speech act of love expressing as well as help the interlocutors find an effective way in dealing with cross-gender communication. We also expect that this study could be a useful reference for other pragmatists.